2008
DOI: 10.1021/bm8002557
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Insulin Aggregation by Heparin

Abstract: The aggregation of insulin near its isoelectric point and at low ionic strength was suppressed in the presence of heparin. To understand this effect, we used turbidimetry and stopped-flow to study the pH-and ionic strength (I)-dependence of the aggregation of heparin-free insulin. The results supported the role of interprotein electrostatic interactions, contrary to the commonly held view that such forces are minimized at pH ) pI. Electrostatic modeling of insulin (DelPhi) revealed that attractive interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 66 publications
4
65
0
Order By: Relevance
“…Several globular proteins have maximum free energy change ∆ G unf (8 -17 kcal/mol) in a temperature range between 10 and 40 ° C, including basic pancreatic trypsin inhibitor, CT, cytochrome c, lysozyme, metmyoglobin, RNase A, and trypsin. 99 Therefore, some proteins could aggregate easily at room temperature, such as insulin 100 and a therapeutic immunoglobulin. 101…”
Section: Relationship Between Temperature and Protein Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Several globular proteins have maximum free energy change ∆ G unf (8 -17 kcal/mol) in a temperature range between 10 and 40 ° C, including basic pancreatic trypsin inhibitor, CT, cytochrome c, lysozyme, metmyoglobin, RNase A, and trypsin. 99 Therefore, some proteins could aggregate easily at room temperature, such as insulin 100 and a therapeutic immunoglobulin. 101…”
Section: Relationship Between Temperature and Protein Stabilitymentioning
confidence: 99%
“…Recent results suggest that signifi cant protein -protein interactions can still exist from the marked charge anisotropy of protein around its pI, such as insulin. 100 Nevertheless, the rate and extent of protein aggregation should be maximal around the pI and should be negatively correlated with the absolute value of charge. 151,152 Indeed, Militello et al 29 found that the aggregation of BSA increased as pD is adjusted closer to its pI (about 5) at 58 ° C. Giger et al 100 studied aggregation of insulin in the pH range of 3 -9 and found that aggregation (turbidity) of insulin at room temperature was fastest at pH 5.6 (pI = 5.5) in a 10 mM NaCl solution.…”
Section: Protein Aggregation Versus P Imentioning
confidence: 99%
See 2 more Smart Citations
“…The anodic peak arises from the formation of AuO x and the cathodic peak corresponds to the reductive process. 20,21 Compared with curve A, bovine insulin (Fig. 1, curve B) has an increased anodic peak near 1.20 V, but a stable cathodic peak near 0.70 V. So this anodic peak should not only be attributed to the electrochemical oxidation of Au electrode but also be assigned to the oxidation of insulin.…”
Section: Cyclic Voltammetry Analysismentioning
confidence: 96%